Kesesuaian Rencana Pelaksanaan Pembelajaran (RPP) dengan Pelaksanaan Pembelajaran Bahasa Jawa di SMP Se-Kecamatan Pulosari Kabupaten Pemalang - Setiyasih, Rezkina Mega (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2016)
One of the problems in the implementation of the 2013 curriculum for learning javanese is the lack of teacher’s understanding about the curriculum so that effects on the preparation lesson plan and learning implementation. This research aimed to describe the suitability of the learning with teacher’s lesson plan in junior high school pemalang district of pulosari. The result of the research are lesson plan javanese teachers is in conformity with Permendikbud number 65 of 2013, but on the basis of verbal messages delivery competence indicator, there is no indicators that make basic competence is achieved so that the learning objectivies have been achieved. Implementation of learning components that are in accordance with lesson plan is materials, methods, assessment, approaches. There is a mismatch between lesson plan and implementation of the javanese learning is on time allocation component, approaches, methods, media, materials, step of learning in core activitis and assessment.